THE ROLE OF THE PALM OIL INDUSTRY IN SUPPORTING INDONESIA’S ECONOMIC RESILIENCE AND DEFENSE LOGISTICS - Hutagalung, Remond Tumpak Sumurung; Tumanggor, Muliahadi; Iswati, Sri (jfpublisher, 2025)
This study aims to examine the strategic contribution of the palm oil industry to Indonesia’s economic resilience and defense logistics system. Employing a qualitative approach based on literature review, the analysis draws upon academic sources, policy documents, and institutional reports. As a leading sector in export and alternative energy supply, the palm oil industry plays a vital role in supporting national fiscal stability through state revenue generation and employment creation. Furthermore, the geographic distribution of palm oil plantations across border regions and remote areas has the potential to strengthen defense logistics infrastructure, particularly in resource mobilization and operational support. This study also highlights the opportunity to utilize palm-based bioenergy as an alternative fuel to sustain military operations. The findings indicate that synergy among industrial, fiscal, and defense policies is essential to optimize the strategic role of palm oil in enhancing national resilience. The study recommends reinforcing cross-sectoral regulations and increasing investment in downstream palm oil development aligned with strategic national interests.